The meaning of fashion in the song “Made You Look” by Meghan Trainor: A semiotic analysis of Charles Sanders Peirce - Zakiyah, Amanda Arichah (Maliki Interdisciplinary Journal, 2024)
Fashion is a primary need that cannot be separated from everyone's life. The reason is because fashion represents the personality and feelings of each person. In addition, through fashion, there is a message that the wearer wants to convey so that it influences other people's views of him. Therefore, this article was created with the aim of knowing the meaning of fashion signs and symbols in song lyrics as a source of research data. The lyrics for the song are titled "Made You Look" by Meghan Trainor. In this song, the singer (Meghan Trainor) wants to convey a message and express her feelings about fashion through the lyrics. When collecting the data, the researcher uses text analysis techniques and literature studies. For the research method, the researcher used a qualitative-descriptive. Meanwhile, the theory used is Charles Sanders Peirce's semiotic theory. Charles Sanders Peirce's semiotic concept is famous with his theory of the trichotomy of meaning, which consists of three main elements: sign, object, and interpretation. Through this concept, when analyzing song lyrics, it can be concluded that fashion greatly influences everyone's self-confidence.